National identity, partisanship and populist protest as factors in the 1999 Australian republic referendum - Charnock, David (Routledge, Taylor & Francis, 2001)
Using survey data from the Australian Constitutional Referendum Study 1999 (ACRS99), I begin by showing that the votes of direct electionists were as important as those of monarchists in the defeat of the Republic referendum. Since these votes were crucial to the outcome, I then discuss several possible explanations of what differentiated those direct electionists who voted against the referendum proposal from those who voted in favour. Explanations considered include partisan influences, populist protest, and the role of national identity and ancestry. I find that all had a part to play in distinguishing the direct electionists who supported the referendum from those who did not, with the protest aspect being related to conceptions of national identity and capable of being interpreted as a reaction against multiculturalism. I also consider future prospects and argue that eventually some sort of direct election outcome is likely.